Water contamination emergencies : collective responsibility - Gray, J. 1947-; Thompson, K. C. 1944- (Royal Society of Chemistry, 2009)
By leading experts, this is an up-to-date view of the strategies essential for an effective response to water contamination emergencies. In the current international situation, the ability to deal effectively with water contamination emergencies is of rapidly increasing importance. The third in a series of conference proceedings, this book brings together contributions from leading scientists and experts in industry and academia. It offers an international perspective and develops the themes of the previous volumes entitled Water Contamination Emergencies: Can we cope? and Water Contamination Emergencies: Enhancing our response. The full range of potential chemical, microbiological and radiological contamination scenarios are addressed from the perspective of medical and health professionals, water companies and regulators, environmental protection professionals, risk and business continuity managers, emergency planners, local authorities, service and support providers, detection and equipment suppliers, disaster recovery specialists, water security experts, water distribution modellers and laboratories involved in round the clock emergency response. Emphasis is placed on the considerable effort required to prepare for and respond to an emergency. It is not sufficient for Individuals to simply identify their own responsibilities, they must also take action to establish effective and efficient working relationships with the other parties involved. In other words, they must take "Collective Responsibility". In summary, this book will provide readers with an up-to-date view of current strategies and the collaboration essential for an appropriate and timely response to water contamination emergencies
"The proceedings of the International Conference on Water Contamination Emergencies: Collective Responsibility held at the Royal Society of Medicine, London on 7-8 April 2008"--Title page verso
Keywords: Water -- Pollution -- Congresses.; Water -- Pollution -- Prevention -- Congresses.; Water -- Pollution -- Health aspects -- Congresses.; Emergency management -- Congresses.; Public health.; Medical emergencies.; Emergency management.; Environmental monitoring.; Disasters.; Health.; Pollution.; Medical care.; Medical personnel.; Diseases.; elektronické knihy; electronic books